Analyzing genetic factors contributing to dysmotility in Hirschsprung’s disease and African Degenerative Leiomyopathy in a South African population - Maluleke, Twananani (Stellenbosch : Stellenbosch University, 2019)
Thesis (MSc)--Stellenbosch University, 2019.